Relationship of vitamin B12, folic acid and homocysteine level with time domain measures of heart rate variability in female Metabolic Syndrome - Akter, Khaleda; Sultana, Shamima; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2022)
Background: Metabolic syndrome (MetS) is a major risk factor for cardiac mortality and morbidity. Hyperhomocysteinemia and folic acid are related with MetS. Both MetS and hyperhomocysteinemia adversely affect heart rate variability (HRV). Objectives: To assess the relationship of vitamin B12, folic acid and homocysteine levels with HRV in female MetS patients. Methods: This cross sectional study was carried out on 40 female MetS patients of 25-45 years of age. Forty apparently healthy female with similar age were control. Chemiluminescent immunoassay measured serum vitamin B12, folic acid, homocysteine level and time domain parameters of HRV were recorded by Powerlab 8/35, AD instruments, Australia. Independent sample ‘t’ test and pearson correlation coefficient test was used for statistical analysis Results: In this study, all the time domain HRV variables ( Standard deviation of all RR intervals-SDRR, Coefficient variation of RR interval-CVRR, The square root of mean squared difference of RR intervals-RMSSD and Number of R-R interval differing >50ms from adjacent intervals divided by the total number of all R-R intervals-pRR50%) were significantly lower (p<0.05) in MetS patients compared to control. But correlation analysis showed only the folic acid level was significantly negatively correlated (p<0.05) with SDRR, CVRR, RMSSD and pRR50%. Conclusion: The result of this study showed inverse relation of low HRV with low serum folic acid levels in female MetS patients. J Bangladesh Soc Physiol. 2022, June; 17(1): 41-48